2017
DOI: 10.22159/ijpps.2017v9i3.16402
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and Hypolipidemic Effects of Annona Muricata L. Leaf Ethanol Extract

Abstract: Objective: The aim of this study was to investigate hypoglycemic and hypolipidemic effects of Annona muricata leaf ethanol extract. This study also investigated phytochemical analysis of the extract and improvement in the islet of Langerhans.Methods: Hypoglycemic and hypolipidemic effects were evaluated using alloxan induced diabetic rats. Twenty-five Wistar rats devided into five groups, that are normal group, control group that induced by alloxan 125 mg/kg body weight and given CMC (carboxymethyl cellulose),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
2
6
0
2
Order By: Relevance
“…Sperm motility relies on the coordinated propagated flagella wave that is under the influence of acetylcholinesterase [12]. The spermatozoa motility is energy dependent, fueled by fructose and glucose oxidation, so reduction in the progressive sperm motility of the treated rats seen in this study could be due to the acetylcholinesterase inhibition and hypoglycemic properties of the specie of this plant as reported Sovia et al [13]. The significant decrease in the sperm concentration supported by the various degrees of degeneration in the histologic sections of the testis, suggests that Annona muricata methanolic bark extract is capable of permeating the blood-testis barrier [14].…”
Section: Discussionsupporting
confidence: 61%
“…Sperm motility relies on the coordinated propagated flagella wave that is under the influence of acetylcholinesterase [12]. The spermatozoa motility is energy dependent, fueled by fructose and glucose oxidation, so reduction in the progressive sperm motility of the treated rats seen in this study could be due to the acetylcholinesterase inhibition and hypoglycemic properties of the specie of this plant as reported Sovia et al [13]. The significant decrease in the sperm concentration supported by the various degrees of degeneration in the histologic sections of the testis, suggests that Annona muricata methanolic bark extract is capable of permeating the blood-testis barrier [14].…”
Section: Discussionsupporting
confidence: 61%
“…Chronic hyperlipidemia in T2DM leads to an abnormal hepatic lipid metabolism and causes excess fat to accumulate, ultimately leading to NAFLD [38]. In previous studies, AME supplementation alleviated dyslipidemia in T2DM, especially through lowering hepatic triglycerides and plasma LDL cholesterol levels [25,38,39]. In accordance with the previous studies, this study demonstrated that, low dose of AME supplementation significantly reduced the hepatic TG concentration in the T2DM mice.…”
Section: Discussionsupporting
confidence: 88%
“…Muricata Annona L. (Graviola), a member of the Annonaceae family, is a perennial tree species used as herbal medicine. The plant has various pharmacological functions, including cytotoxicity, antimicrobial, and wound care [14]. It has antidiabetic and hypolipidemic [15], antiarthritic [16], antinociceptive [17], hepatoprotective and bilirubin-lowering [18], powerful antioxidants activities [19], antihypertensive [20], anticancer [21], gastroprotective [22], and anti-inflammatory and anticonvulsant [23] effects.…”
Section: Introductionmentioning
confidence: 99%